Disconnection and Well-being of Indigenous People - Peacock, Ellen (City University of Seattle (CityU), 2021)
The purpose of this literature review is to understand what disconnection means for Indigenous people and to understand what we presently know about addressing this disconnection. Since colonization, Indigenous people have experienced disconnection in various ways such as forced assimilation. Through multiple facets of assimilation and policies that enforce assimilation, a disconnect has been created for many Indigenous people from culture, tradition, language, land, and community. The author analyzed nine qualitative studies and one mixed-methods study. The author analyzed the strengths and weaknesses of the methodology used within the studies. From the findings emerged four themes: a) the use of the medicine wheel as a holistic approach; b) connection to the land and healing; c) tradition and spirituality; d) resilience and reclamation. The themes that emerged are all relevant to approaches that are beneficial in promoting Indigenous well-being. As well, the author examines the ethics within the 10 selected studies. Finally, the author discusses the present context, clinical application, and recommendations for future research. This literature review demonstrates that utilizing non-Western approaches promotes well-being for Indigenous people.